GENDER: INTEGRATING CRIMES AGAINST WOMEN INTO INTERNATIONAL CRIMINAL LAW - Mohammad Irfan (Jurnal Pembaharuan Hukum, 2018)
The author identifies the major goals and achievements in the area of recognizing women as full subjects of human rights and eliminating impunity for gender crimes, highlighting the role of non-governmental organizations ("NGO's"). Until the 1990s sexual violence in war was largely invisible, a point illustrated by examples of the "comfort women" in Japan during the 1930s and 1940s and the initial failure to prosecute rape and sexual violence in the ad hoc international criminal tribunals for the former Yugoslavia and Rwanda. Due in a significant measure to the interventions by NGOs, the ad hoc international criminal tribunals have brought gender into mainstream international jurisprudence. For example, the Yugoslavia tribunal has devoted substantial resources to the prosecution of rape and explicitly recognized rape as torture, while the Rwanda tribunal has recognized rape as an act of genocide. Elsewhere, the Statute of the International Criminal Court is a landmark in codifying not only crimes of sexual and gender violence as part of the ICC's jurisdiction, but also in establishing procedures to ensure that these crimes and their victims are properly treated. Working towards this end the Women's Caucus for Gender Justice met with significant opposition. It persisted because of the imperative that sexual violence be seen as part of already recognized forms of violence, such as torture and genocide.